Evaluation of Shared Experiences Among Patients and Providers Following Behavioral Health Integration in Primary Care. (November 2021) - Kenton, Natalie; Bouranis, Nicole; Cox, Emily J.; Jacobson, Laura; Wright, Bill J
Behavioral health integration (BHI) changes the paradigm of primary care delivery by integrating behavioral healthcare into primary care. Thus, BHI likely alters the shared experiences of both patients and providers in an interrelated manner; however, their experiences are usually evaluated separately. The purpose of this study was to analyze these shared experiences together within patient–provider pairs in integrated clinics. First, patient interviews were conducted using semi-structured interview guides and transcripts were analyzed for major themes of patient experience. Next, providers named in patient interviews were interviewed around these same themes. Thematic analysis was performed on 18 transcripts (11 patients, 7 providers). Common themes included BHI experience, pain management, feeling heard by providers, and health care experiences. Areas of alignment included positive perception of BHI, an absence of long-term care, and a desire to share decision-making. Pain management was a persistent area of conflict, and the differing experiences were consistent with a change in the psychodynamic patient–provider model. This conflict highlights a gap in BHI and a need for provider education about psychodynamic relationship models.